Evaluation of Urinary Iodine Excretion during Gestation in Urban Residents of Urmia County - V Jalili; Z Ashrafi; R Enezaremahdi; HR Khalkhali; J Nouroozzade (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2016)
Introduction: Biosynthesis of thyroid hormone and consequently the requirement for iodine have been established to increase during gestation mainly due to increased iodine demand by the fetus. Therefore, diminished iodine intake by the mother during early pregnancy eventually leads to the development of iodine deficiency disorders(IDDS)  in the offspring. The present study aimed to explore the pattern of urinary iodine excretion during gestation in urban districts of Urmia County.